2020
DOI: 10.1108/bfj-04-2019-0260
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' willingness to adopt genetically modified foods

Abstract: PurposeThis study investigates consumers' willingness to adopt genetically modified foods (GM) and the role of innovation and behavioral determinants.Design/methodology/approachA new integrated model that expands the Health Belief Model (HBM) into the Innovation Diffusion Theory (IDT) was developed and examined. A total of 241 consumers were selected from the capital of Iran, Tehran, through a multistage random sampling. The data were analyzed using SEM-PLS modeling.FindingsThe extended HBM model was able to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 69 publications
1
13
0
Order By: Relevance
“…This is consistent with the Theory of Reasoned Action which suggests that consumer intention determines the performance of a specific behaviour (Ajzen, 1985;Quevedo-Silva et al, 2016;Teng & Wang, 2015). Various studies reported a positive and significant correlation between consumer intention and actual purchase behaviour (Ardekani et al, 2020;Follows & Jobber, 2000;Morwitz & Schmittlein, 1992;Wee et al, 2014). Based on the preceding discussion, it was, therefore, hypothesised that: H5: Consumer intention has a positive effect on actual purchase behaviour towards imported grocery products.…”
Section: Development Of Research Hypotheses and Research Modelsupporting
confidence: 79%
“…This is consistent with the Theory of Reasoned Action which suggests that consumer intention determines the performance of a specific behaviour (Ajzen, 1985;Quevedo-Silva et al, 2016;Teng & Wang, 2015). Various studies reported a positive and significant correlation between consumer intention and actual purchase behaviour (Ardekani et al, 2020;Follows & Jobber, 2000;Morwitz & Schmittlein, 1992;Wee et al, 2014). Based on the preceding discussion, it was, therefore, hypothesised that: H5: Consumer intention has a positive effect on actual purchase behaviour towards imported grocery products.…”
Section: Development Of Research Hypotheses and Research Modelsupporting
confidence: 79%
“…Furthermore, Chivandi and Maziriri (2017) examined food safety standards recognition and implementation in Zimbabwean branded fast-food outlets from the perspectives of consumers, staff, and management. Ardekani et al (2020) looked at consumers' willingness to adopt genetically modified foods. Jia (2020) contrasted restaurant tourists' motivation and satisfaction from China and the United States by evaluating their online ratings and reviews.…”
Section: Introductionmentioning
confidence: 99%
“…This result revealed that farmers would have a more positive attitudes toward GM crops if they perceived greater self-efficacy related to the farming of GM crops. Ardekani et al (2020) and Bimbo et al (2017) highlighted the importance of this factor in determining the willingness of consumers to adopt GM foods and dairy products. Government support (β = 0.276, t = 3.495, p = 0.001) was listed as the second most important predictor of attitudes towards GM crops.…”
Section: Resultsmentioning
confidence: 99%